2010
DOI: 10.1179/acb.2010.009
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hemiplegia Caused by a Retrograde Cerebral Venous Air Embolism After Central Venous Catheter Removal: An Illustrative Case.

Abstract: Central venous catheters are widely used in clinical practice. Air embolism is a rare, but potentially life threatening complication of central venous catheterisation. We describe a case of collapse and transient hemiplegia after removal of central venous catheter. This was accidentally performed with the patient in upright position. A CT scan of the brain demonstrated air in the sinus cavernosus bilaterally and at the posterior wall of the foramen magnum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Cerebral venous air embolism occurs mostly because of air entry into the brain veins due to some mechanism, including trauma [ 1 5 ], central venous catheterization [ 6 , 7 ], epidural catheterization [ 8 ], and administration through the chest drainage tube [ 9 ]. In most cases of cerebral venous air embolism caused by head trauma, computed tomography (CT) scan showed the skull fractures and the air might enter through the fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral venous air embolism occurs mostly because of air entry into the brain veins due to some mechanism, including trauma [ 1 5 ], central venous catheterization [ 6 , 7 ], epidural catheterization [ 8 ], and administration through the chest drainage tube [ 9 ]. In most cases of cerebral venous air embolism caused by head trauma, computed tomography (CT) scan showed the skull fractures and the air might enter through the fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Bowles et al reported paradoxical air embolism in a patient who underwent pulmonary artery catheter removal [ 12 ]. Various case reports exist wherein cerebral air embolism occurred secondary to central venous access removal, some with right-to-left shunting and others without [ 15 – 18 , 24 , 25 ]. Harlan et al even reported a spontaneous air embolism in a patient with a pulmonary arteriovenous malformation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk that ancient (and poorly glycosylated) influenza variants re-emerge among the human population is a major concern. In particular, a novel H1N1 influenza strain caused an outbreak in 2009 in Mexico, Canada and USA, leading to severe symptoms in younger patients and mild ones in elders ( 101 ). Wanzeck et al.…”
Section: Glycan Masking Other Applicationsmentioning
confidence: 99%